2008
DOI: 10.4314/bcse.v22i3.61218
|View full text |Cite
|
Sign up to set email alerts
|

<b>Synthesis, screening and QSAR studies of 3-benzoyl-2-oxo/thioxo-1,2,3,4-tetrahydro-pyrimidine analogues as antibacterial agents</b>

Abstract: The purpose of this study was to synthesize several 3-benzoyl-5-acyl-6-methyl-4-substituted-2oxo/thioxo-1,2,3,4-tetrahydropyrimidines, evaluate them for their antibacterial activity and to establish correlation between the activity and physicochemical properties. 5-Acyl-6-methyl-4-substituted-2-oxo/thioxo-1,2,3,4tetrahydropyrimidines (A) were synthesized by cyclocondensation reaction between appropriate aldehyde, acetoacetate and urea/thiourea in presence of aluminium chloride and hydrochloric acid which upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The same research group also investigated the results using the QSAR approach and observed a good correlation between the structural features and biological activity. They concluded that molecules with a less positive partial charge and a negative polar Van der Waals surface area make a higher contribution rather than the ratio of Van der Waals surface area to molar refractivity (119). A substituted benzoyl methyl thio group located on the C-2 position of the THPM ring seemed to be effective in the antimicrobial activity, as effective as a moiety located on N-3 position.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The same research group also investigated the results using the QSAR approach and observed a good correlation between the structural features and biological activity. They concluded that molecules with a less positive partial charge and a negative polar Van der Waals surface area make a higher contribution rather than the ratio of Van der Waals surface area to molar refractivity (119). A substituted benzoyl methyl thio group located on the C-2 position of the THPM ring seemed to be effective in the antimicrobial activity, as effective as a moiety located on N-3 position.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…This method represented a simple and efficient synthesis of complex molecules based upon one-pot, multi-component condensation reaction between thiourea/urea, appropriate aldehydes and b-ketoesters under strong acidic conditions [14,15]. Further, several new improved procedures for the classical method using Lewis acids, such as combination of aluminium chloride and hydrochloric acid (HCl) [16], BF 3 ÁOEt 2 [17], low-melting tartaric acidurea mixtures [9], metal triflates [18,19], zeolites [20], strong protic acids like HCl [21,22] and sulfuric acid (H 2 SO 4 ) [21] have been developed; also, microwave- [23] and ultrasonic-assisted methods [24] have been developed. Moreover, Friot et al [25] reported that S-methylthioimines or its iodide salts reacted with acrylic dienophiles or ketenes in the presence of triethylamine to give methylthiodihydropyrimidines/methylthiotetrahydropyrimidines with good yields.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrimidine fragment is present in various biologically active compounds, many of which are used therapeutically [1][2][3]. Thus, much attention has been paid to derivatives of pyrimidines, including their hydrogenation products.…”
Section: Introductionmentioning
confidence: 99%